Type 2 innate lymphoid cells are not involved in mouse bladder tumor development - Schneider, Anna K.; Domingos-Pereira, Sonia; Cesson, Valérie; Polak, Lenka; Fallon, Padraic G.; Zhu, Jinfang; Roth, Beat; Nardelli-Haefliger, Denise; Derré, Laurent (Frontiers in Immunology, 2024)
Therapies for bladder cancer patients are limited by side effects and failures, highlighting the need for novel targets to improve disease management. Given the emerging evidence highlighting the key role of innate lymphoid cell subsets, especially type 2 innate lymphoid cells (ILC2s), in shaping the tumor microenvironment and immune responses, we investigated the contribution of ILC2s in bladder tumor development. Using the orthotopic murine MB49 bladder tumor model, we found a strong enrichment of ILC2s in the bladder under steady-state conditions, comparable to that in the lung. However, as tumors grew, we observed an increase in ILC1s but no changes in ILC2s. Targeting ILC2s by blocking IL-4/IL-13 signaling pathways, IL-5, or IL-33 receptor, or using IL-33-deficient or ILC2-deficient mice, did not affect mice survival following bladder tumor implantation. Overall, these results suggest that ILC2s do not contribute significantly to bladder tumor development, yet further investigations are required to confirm these results in bladder cancer patients.